Ion selective electrodes based on chalcogenide glasses - Conde Garrido, Juan Manuel (2010)
The properties of chalcogenide glasses as sensitive membranes in ion selective electrodes (ISEs) have been investigated. It is shown that ISEs based on the AgGeSe system show sensitivity to the presence of Ag+ and Cu2+ ions in aqueous solutions and in both cases they exhibit super-nernstian responses. The analytical properties such as reproducibility, linear range, sensitivity and detection limit were studied. The response of the electrodes is apparently conditioned by the amount of Ag in the membrane. The addition of Cu to the membrane composition does not improve the sensitivity of the electrodes. The sensitivity to Cu2+ ions of thin film ISEs of composition (AgCu)GeSe was found to be smaller than the one of bulk ISEs, but still super-nernstian.